How authentic are assessments in vocational education? An analysis from Chilean teachers, students, and examinations - Villarroel, Verónica; Melipillán, Roberto; Santana, Javiera; Aguirre, Diego (Frontiers in Education, 2024)
Authentic assessment promotes professional skills, bridging the gap between academic knowledge and real-world scenarios. Given the challenges faced by vocational education in Chile, there is a keen interest in assessment methods within both secondary schools and higher education institutions. The study's sample included 244 students, 37 teachers, and a compilation of 905 questions sourced from written examinations. The findings reveal certain disparities in perspectives between teachers, students, and the examinations reviewed. On one hand, secondary vocational education teachers perceive the quality of assessments to exceed those of their counterparts in higher vocational education. Conversely, students in higher vocational education express a heightened sense of depth and engagement in their learning compared to their secondary vocational education peers. Upon examination of the assessments, it becomes evident that while written examinations are more prevalent in secondary vocational schools, these often involve open-ended and analytical inquiries. In contrast, higher vocational education institutions predominantly rely on closed-response questions that lean towards rote memorization. However, when these questions are open-ended, they are more oriented towards the transfer of knowledge compared to the secondary vocational education level. The level of realism is more pronounced in higher vocational education than in secondary vocational education. Both educational tiers exhibit gaps in attaining the principles of authentic assessment.